2003
DOI: 10.1542/peds.111.5.939
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Volumes and Their Later Neurodevelopmental Correlates in Term and Preterm Infants

Abstract: These findings of reduced volumes in sensorimotor and parieto-occipital regions in preterm infants, and the prospective correlations of regional volumes with cognitive outcome, confirm and extend findings previously reported in a cross-sectional study of 8-year-old prematurely born children. The data suggest that regional brain volumes near term are a promising marker for predicting disturbances of cognitive outcome in preterm infants. Further prospective, longitudinal studies of neonatal brain volumes and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
281
6
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 398 publications
(308 citation statements)
references
References 29 publications
14
281
6
7
Order By: Relevance
“…An alternative definition of parcels may also improve sensitivity to differences in myelination, because myelination follows an anatomically specific developmental process. 62 Similar to the current study, Peterson et al 47 reported findings of decreased white matter in the central region, which includes the sensor-motor system, as well as the auditory processing areas of the frontotemporal lobes. In addition, the preterm infants in that study displayed decreased white matter volumes in the parieto-occipital regions when compared with term infants.…”
Section: Effects Of Premature Birth On Total and Regional White Mattesupporting
confidence: 87%
See 3 more Smart Citations
“…An alternative definition of parcels may also improve sensitivity to differences in myelination, because myelination follows an anatomically specific developmental process. 62 Similar to the current study, Peterson et al 47 reported findings of decreased white matter in the central region, which includes the sensor-motor system, as well as the auditory processing areas of the frontotemporal lobes. In addition, the preterm infants in that study displayed decreased white matter volumes in the parieto-occipital regions when compared with term infants.…”
Section: Effects Of Premature Birth On Total and Regional White Mattesupporting
confidence: 87%
“…Several investigations in preterm infants with brain injury have identified an association between increased CSF volumes and decreased cerebral volumes. 11,13,47 The current study provides the first evidence to suggest that, in lowrisk preterm infants, those selected to have a head circumference appropriate for their PMA, cerebral volume is normal, yet CSF volume is increased. Considering that an appropriate head circumference between the 10th and 90th percentile corresponds with 33-to 38-cm head circumference measured at birth, this gives a broad range of variable brain tissue and CSF volumes, which may obscure true group differences in a small cohort.…”
Section: Effects Of Premature Birth On Intracranial Cerebral and Csmentioning
confidence: 64%
See 2 more Smart Citations
“…Some studies of these at risk infants demonstrate abnormality in gyral grey matter development, marked by decreased gray matter volume. [453][454][455][456] This loss of grey matter may reflect neuronal cell loss and diminished dendritic growth and synaptogenesis. 457,458 Diminished head growth has been associated with cognitive delay and behavioral deficits.…”
Section: Discussionmentioning
confidence: 99%